Monitoring Nilai Kritis Tekanan Sistolik Dan Diastolik Pada Asuhan Keperawatan Gagal Ginjal Kronik Yang Dilakukan Hemodialisis Jenis Arteriovena Shunt Cimino Dan Akses Femoral Cephalica - Martono Martono (Interest : Jurnal Ilmu Kesehatan, 2017)
Abstract: Systolic Pressure, Diastolic, Hemodialysis. Renal function at a more serious stage of the remnants of the metabolism could not be removed from the body, besides that, however, the kidneys can no longer change K / H for Na that resulted in an increase in the amount of potassium that machine that later can be triggered the interruption the heart. Hemodialysis is one of the alternative solutions that can be done when the kidneys experiencing the inability to mengekresikan debris from the remnants of the metabolism of the body. This research aims to clarify the picture changes critical value systolic pressure and diastolic pressure that done arteriovenous Cimino shunt type of hemodialysis and femoral access cephalic nursing nursery on chronic renal failure. This is the explanatory research design research with cross-sectional approach. A sample of this research is to patients with chronic renal failure undergoing hemodialysis which numbered 44 samples with sampling techniques using purposive sampling. This research statistics tests using descriptive test with the level of the significance of 95 %. The results of the study showed that the patients who performed hemodialysis aged candidates are age ≥51 about 59 percent and the age of the youngest 29 years and oldest 77 years, which dominated gender male.57 percent patients who do good hemodialysis AV Shunt or dialysis access Cephalica Femoral most no change in systolic pressure and diastolic pressure or settled.